IDIOMATIC EXPRESSION IN DANGEROUS ALBUM BY MICHAEL JOSEPH JACKSON - Laia, Sri Indah Wahyuni (Universitas Nias Raya, 2022)
Idiom are forms of speech that meaning cannot be interpreted literally or from their constituent elemens. idiomatic expression can be found in everyday conversation as well as in some literary works, such as novels, poems and song lyrics from various albums. This research was aimed to analyze the idiomatic expression in Dangerous album by Michael Joseph Jackson. This research was designed by using qualitative research. While, the data of this research is idiomatic expression in Dangerous album by Michael Joseph Jackson. The procedures used during analyzing the data were preparation, reading process, coding, description and interpretation. Based on data analysis it was found that there were six type of idiomatic expression,there are similes, binomials, proverbs, euphemism, cliche and fix statement. The idiom expression found in the Dangerous album tends to compare human or something with nature, food and stuff. While meaning is to motivate, persuade, and convey the messages that the song in this album sound interesting. The research suggets English teacher, student, and readers to use this research as the reference to increase their knowledge about idiomatic expression. Also the readers to use this research as a guidance in conducting the relevant research to sharpen and enlarge their literal development by trying to understand the whole context of lyric.